Queering Genocide: Israel’s Pinkwashing Campaign and the Ineptness of International Law in Gaza - El Amoor, Izat (SQS – Suomen Queer-tutkimuksen Seuran lehti, 2024)
Immediately after the Hamas attack on Israel on October 7, 2023, as the escalation grew into a war, then the war into a genocide, Israel and its Zionist allies invoked queer Palestinians to vindicate the genocide in Gaza using a largescale pinkwashing campaign. Being an Israeli colonial practice that queer Palestinians have constantly reframed in service of the wider Palestinian struggle against occupation and apartheid, pinkwashing pre- and post-October 7 has been largely akin. Considering the severity of the Zionist colonial violence since October 7, however, the queer Palestinian response to Israeli pinkwashing reemerged with the added merit of challenging the failures of genocide discourse in both international law and academia. This article presents a media analysis of (1) Israel’s actions to pinkwash genocide; (2) the pro-Palestine anti-pinkwashing (pinkwatching) organizing that emerged from the anti-genocide transnational movement, and finally; (3) I contextualize the two to argue that, besides the irremovable link between Palestinian queer liberation and collective Palestinian decolonization, it is beneficial for international law and genocide studies to integrate queer perspectives/analyses in documenting, analyzing, and explaining the failures to prevent Israel’s genocide and protect the Palestinians.